Effect of Polypropylene Fiber on the Flexural Strength Properties of Lightweight Foam Mixed Soil - Raksiri Sukkarak; Pornkasem Jongpradist; Pitthaya Jamsawang; Piti Sukontasukkul; Prinya Chindaprasirt (Advances in Materials Science and Engineering)
This study examines the effect of polypropylene fiber on the flexural strength properties of lightweight foam mixed soil (LFS). The flexural properties of LFS comprising different proportions of polypropylene fiber (58 mm) at different volume fractions (0.5%, 0.75%, and 1%), three different cement contents of 100, 150, and 200 kg/m3, and densities of 0.8, 1.0, and 1.2 g/cm3 were thoroughly investigated. The flexural performance of LFS according to ASTM C1609 was achieved after 28 days of aging. The results show that the flexural characteristics of LFS could be enhanced by fiber additives, as indicated by the increase in the flexural/residual strength and equivalent flexural strength ratio. The flexural performance is also related to the mixing components, including the density and cement content. For the toughness behavior, the equivalent flexural strength ratio reached up to 100%, which could be achieved with the strain-hardening specimens. The fiber inclusion is more efficient with an increase in the density and cement content of specimens as shown by the overall rating of the flexural performance.